Elevated Granulocyte Colony-Stimulating Factor, Non-Infectious Leukocytosis and Fevers in a Patient with Multiple Myeloma - Sebasky, Meghan M. (Springer-Verlag, 2008)
Background: We report the case of a 56-year-old male with multiple myeloma in whom recurrent fevers and leukocytosis delayed potentially effective chemotherapy due to concern for active infection. Design and measurements: A thorough infectious workup, including CT and PET scans, was negative. The patient was eventually found to have an elevated serum granulocyte colony-stimulating factor (G-CSF) of 113 pg/ml (normal range 0.0 – 39.1 pg/ml), which was likely the cause of his persistent leukocytosis and fevers. Multiagent chemotherapy was initiated, and the fevers resolved in the next 4 days. Results: Leukocyte concentrations trended down after initiation of chemotherapy, but it is uncertain how much of the decline was attributable to immunosuppression. Conclusion: We report this well-documented case to demonstrate that G-CSF production should be considered as a cause of unexplained fever and leukocytosis in patients with multiple myeloma to prevent inappropriate and delayed definitive diagnosis and treatment.